Alliin, a garlic organosulfur compound, ameliorates gut inflammation through MAPK‐NF‐κB/AP‐1/STAT‐1 inactivation and PPAR‐γ activation. Issue 9 (27th April 2017) - Shi, Limin; Lin, Qinlu; Li, Xinhua; Nie, Ying; Sun, Shuguo; Deng, Xiyun; Wang, Long; Lu, Jun; Tang, Yiping; Luo, Feijun
Abstract : The anti‐inflammatory effects and the molecular mechanism of alliin was analyzed in dextran sulfate sodium (DSS)‐induced colitis mice and in a lipopolysaccharide‐stimulated RAW264.7 cell model. The results show that alliin ameliorates DSS‐induced ulcerative colitis and inhibits the inflammatory responses in the examined cells. Abstract : Scope: In this study, the anti‐inflammatory effects and the molecular mechanism of alliin were analyzed in dextran sulfate sodium (DSS)‐induced colitis mice and lipopolysaccharide‐stimulated RAW264.7 cell model. Methods: The phenotype of mice was recorded in the DSS‐induced and/or alliin (500 mg/kg) groups. Histopathological alterations were analyzed by H&E staining. MPO and MDA of colon tissues were measured. The mRNA expression levels of inflammatory factors were determined by qRT‐PCR, and protein expressions of inflammatory factors or activation of kinases were determined by Western blotting. Results: Oral administration of alliin significantly inhibited the decrease of body weight, improved the DAI and decreased the infiltration of inflammatory cells in colonic tissues. The content of NO, MDA, and MPO, the expression of iNOS and inflammatory factors as well as MAPK and the phosphorylation of PPAR‐γ were inhibited in alliin‐treated group. Treatment with alliin significantly repressed the expression of inflammatory factors in LPS‐stimulated RAW264.7 cells. Further research demonstrated that alliin repressed LPS‐induced AP‐1/NF‐κB/STAT‐1 activation by inhibiting the phosphorylations of p38, JNK, and ERK1/2‐regulated PPAR‐γ activation. Conclusion: Our results show that alliin ameliorates DSS‐induced ulcerative colitis and inhibits the inflammatory responses in LPS‐stimulated RAW264.7 cells partly through inhibiting ERK1/2‐, JNK‐/PPAR‐γ–stimulated NF‐κB/AP‐1/STAT‐1 activations.